Metode Penanganan Anak Hiperaktif Oleh Guru di Sekolah Dasar Negeri 32 Bengkulu Tengah - Linda Marlensi; Yuli Astuti; Sevi Wahdatun; Rica Andela; Jeli Syah Putri (JPT : Jurnal Pendidikan Tematik, 2025)
This research is motivated by various methods used by teachers in dealing with hyperactive children. In addition, this study aims to determine the methods of handling hyperactive children at public elementary school 32 Pondok Kubang Bengkulu Tengah. In this study, researchers used a qualitative descriptive approach. Data collection techniques in this study used observations and interviews. Research informants were taken using a purvosive sampling technique. The results showed that the handling methods carried out by teachers at SDN 32 Pondok Kubang, Central Bengkulu were by changing seating positions, providing subject matter and information with clear and repeated instructions as necessary, giving assignments that were appropriate to student learning styles and giving extra time to complete assignments, and ensuring that the child with ADHD has a notebook for each subject. The obstacle experienced by SDN 32 Pondok Kubang, Central Bengkulu is that they do not have a special teacher to teach these hyperactive children. So they handle hyperactive children as best they can.